PERANAN BANK DUNIA TERHADAP PRIVATISASI SEKTOR AIR DI INDONESIA PADA TAHUN 1998-2010 - Riris Tri Yunita; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study will discuss the role of the World Bank in support of the privatization of thewater sector in Indonesia. Commencement of water privatization in Indonesia in 1998 at theinitiative of the World Bank offer loans. Water resources sector reform process began in 1999.This process begins with setting up the new water resources law to replace the Water Act. DraftWater Management Act emerged as a prerequisite World Bank loan. Data collection techniquesused in this study is a multi case study. linking theory with data obtained through the researchlibrary (library research). data obtained from books, journals, magazines, newspapers and othersources (document analysis). I also use the internet facility in the process of data collectionrelated and relevant to the issues discussed in this study.The author uses the theory of international organizations. International organizationscan be interpreted as a formal bond that transcends national boundaries are set to form aninstitution in order to facilitate cooperation between the parties involved in the various fields.Implementation explain the concept of economic privatization privatization in many countries isseen as a strengthening of the market in the economic structure of the country. Privatization isan attempt to restore economic activity to the private sector by reducing government interferencein the national economy.Under pressure from the World Bank, the Indonesian government together with theWorld Bank since 1998 put together a program structuring of water in Indonesia is draftinglegislation Water Resources in which the set of policies in the management of the water sectorinclude regulatory and institutional framework, management watersheds and irrigation. Ifpreviously the private sector is only involved in the exploitation and management of drinkingwater, water resources law allows the private sector's role in all areas of water, of water supply,drinking water, until the fulfillment of the raw water for agriculture.Keywords: water privatization Indonesia, the World Bank, international organization theory, the conceptof economic privatization, water resources law.